Virtual screening and biological assay of compound libraries for anticholinesterase activity / Sri Devi D/O Sukumaran - Sukumaran, Sri Devi (2012)
The current research was aimed at finding peripheral anionic site (PAS) binding acetylcholinesterase (AChE) inhibitors to be used in the treatment of Alzheimer’s disease (AD). The crystal structure of human acetylcholinesterase (hAChE) in complex with fasciculin II (2.76 Ǻ) (PDB ID: 1b41) was found to be the most suitable protein for identifying PAS binding ligands in docking studies and was used for virtual screening of about 830 unknown ligands. Twenty-one compounds with a lowest binding energy ranging from -8.7 kcal/mol to -5.6 kcal/mol were selected for testing for AChE inhibitory activity. Four of these compounds were found to inhibit AChE with IC50 values in the range 1–15 μM and two also gave significant inhibition of self-induced amyloid beta (Aβ) aggregation at final concentration of 10 μM. A series of 27 2´-hydroxy-and 2´-methoxy chalcones were also tested and 8 of these compounds were found to inhibit AChE with IC50 values in the range 40–350 μM. Four of them also inhibited self-induced Aβ aggregation at 10 μM. Docking studies showed that all but one of the active compounds appear to be PAS-binding ligands. In summary, we have identified some promising PAS-binding anticholinesterase compounds which show high inhibitory activity towards AChE and self-induced Aβ aggregation. Further studies are required to investigate the effect of these compounds towards AChE-induced Aβ peptide aggregation and determine the inhibition mode of these compounds.